The effect of cement augmentation on pedicle screw fixation under various load cases: results from a combined experimental, micro-CT, and micro-finite element analysis. Issue 12 (8th December 2021) - Chevalier, Yan; Matsuura, Maiko; Krüger, Sven; Traxler, Hannes; Fleege†, Christoph; Rauschmann, Michael; Schilling, Christoph
Abstract : Aims: Anchorage of pedicle screw rod instrumentation in the elderly spine with poor bone quality remains challenging. Our study aims to evaluate how the screw bone anchorage is affected by screw design, bone quality, loading conditions, and cementing techniques. Methods: Micro-finite element (µFE) models were created from micro-CT (μCT) scans of vertebrae implanted with two types of pedicle screws (L: Ennovate and R: S 4 ). Simulations were conducted for a 10 mm radius region of interest (ROI) around each screw and for a full vertebra (FV) where different cementing scenarios were simulated around the screw tips. Stiffness was calculated in pull-out and anterior bending loads. Results: Experimental pull-out strengths were excellently correlated to the µFE pull-out stiffness of the ROI (R 2 > 0.87) and FV (R 2 > 0.84) models. No significant difference due to screw design was observed. Cement augmentation increased pull-out stiffness by up to 94% and 48% for L and R screws, respectively, but only increased bending stiffness by up to 6.9% and 1.5%, respectively. Cementing involving only one screw tip resulted in lower stiffness increases in all tested screw designs and loading cases. The stiffening effect of cement augmentation on pull-out and bending stiffness was strongly and negatively correlated to local bone density around the screw (correlation coefficient ( R ) = -0.95). Conclusion: This combined experimental, µCT and µFE study showed that regional analyses may be sufficient to predict fixation strength in pull-out and that full analyses could show that cement augmentation around pedicle screws increased fixation stiffness in both pull-out and bending, especially for low-density bone. Cite this article: Bone Joint Res 2021;10(12):797–806.